The Antioxidant N-Acetyl-L-Cysteine Restores the Behavioral Deficits in a Neurodevelopmental Model of Schizophrenia Through a Mechanism That Involves Nitric Oxide - Lopes-Rocha, Ana; Bezerra, Thiago Ohno; Zanotto, Roberta; Lages Nascimento, Inda; Rodrigues, Angela; Salum, Cristiane (Frontiers in Pharmacology, 2022)
TThe disruption of neurodevelopment is a hypothesis for the emergence of schizophrenia. Some evidence supports the hypothesis that a redox imbalance could account for the developmental impairments associated with schizophrenia. Additionally, there is a deficit in glutathione (GSH), a main antioxidant, in this disorder. The injection of metilazoximetanol acetate (MAM) on the 17th day of gestation in Wistar rats recapitulates the neurodevelopmental and oxidative stress hypothesis of schizophrenia. The offspring of rats exposed to MAM treatment present in early adulthood behavioral and neurochemical deficits consistent with those seen in schizophrenia. The present study investigated if the acute and chronic (250mg/ kg) treatment during adulthood with N-acetyl-cysteine (NAC), a GSH precursor, can revert the behavioral deficits (hyperlocomotion, prepulse inhibition (PPI) and social interaction (SI)) in MAM rats and if the NAC-chronic-effects could be canceled by L-arginine (250mg/kg, i.p, for 5 days), nitric oxide precursor. Analyses of markers involved in inflammatory response, such as astrocytes (glial fibrillary acid protein, GFAP) and microglia (binding adapter molecule 1, Iba1), and parvalbumin (PV) positive GABAergic, were conducted in prefrontal cortex (PFC, medial orbital cortex (MO) and prelimbic cortex (PrL)) and dorsal and ventral hippocampus (CA1, CA2, CA3, and dentate gyrus (DG)) in rats under chronic treatment with NAC. MAM rats showed decreased time of SI and increased locomotion, and both acute and chronic NAC treatments were able to recover these behavioral deficits. L-arginine blocked NAC behavioral effects. MAM rats presented increases in GFAP density at PFC and Iba1 at PFC and CA1. NAC increased the density of Iba1 cells at PFC and of PV cells at MO and CA1 of ventral hippocampus. Results indicate that NAC recovered the behavior deficits observed in MAM rats through a mechanism involving nitric oxide. Our data suggest an ongoing inflammatory process in MAM animals and support a potential antipsychotic effect of NAC.